Hoya gaoligongensis (Apocynaceae, Asclepiadoideae), a new species from Yunnan, SW China - Zhao, Ming-Xu; Wang, Heng-Ying; Yin, Zhi-Jian; Wang, Meng-Jun; Yang, Jin-Chao; Tan, Yun-Hong (Phytotaxa, 2020)
We describe and illustrate Hoya gaoligongensis M.X. Zhao & Y.H. Tan (Apocynaceae, Asclepiadoideae), a new species native to mid-elevation moist evergreen broadleaved forests of Longling, Yunnan, SW China. We further compare the primary diagnostic morphological characters of H. gaoligongensis to its close relatives, H. yuennanensis Hand.-Mazz. and H. globulosa Hook.f. Compared with these two species, H. gaoligongensis has narrower long-oblanceolate leaves, much smaller lateral vein branch angles, and inconspicuous lateral veins. Although the corolla is similar in all three species, the relative positions of outer and inner corona lobe processes serve as a key character distinguishing these species. A side view of the corona of H. gaoligongensis shows that the outer lobe process is only slightly higher than the inner process, while the corresponding parts of H. yuennanensis are much higher, and those of H. globulosa are at almost equal heights. In addition, the glabrescent leaves and stems of both H. gaoligongensis and H. yuennanensis separate these taxa from H. globulosa.